Long COVID dan Sistem Kardiovaskular - Muhadi, Muhadi; Laksmana, Ivan Mardhi (UI Scholars Hub, 2024)
Even after nasopharyngeal Polymerase Chain Reaction (PCR) swab investigation revealed no COVID-19 infection, some individuals continue to have long COVID symptoms. According to a research published in 2022, 4.5 – 36.6% of patients had symptoms following a COVID-19 infection more than three months. Long COVID symptoms may impact multiple organ systems, including the cardiovascular system. Chest pain, palpitations, arrhythmia, postural orthostatic tachycardia syndrome, and other symptoms are possible appeared in long COVID. D-Dimer, echocardiography, CT scan, cMRI and other supportive test showed meaningful results. Pharmacological treatment can be given based on the concurrent diagnosis found in patients with long COVID. While non-pharmacological treatment can be given in the form of pulmonary rehabilitation, breathing exercises, acupuncture, and COVID-19 vaccination. The state and quality of life of individuals experiencing cardiovascular symptoms following a long COVID infection may deteriorate due to delayed treatment and inadequate early detection.